Letters To the Editor - Rubagumya, G. William; Cupples, Colleen L.; Campfens, Hubert; Roberts, John (Refuge: Canada's Journal on Refugees, 1984)
Please allow me to introduce myself to you: my name is G. William Rubagumya, an attorney in the state of Texas in the USA. I am originally from the country of Rwanda via the refugee camps of Uganda and I have been in the USA for the last 7 years. As you may have guessed, my concern is with the refugees that I left behind both in Ugan- da and other surrounding countries. Myself and other Rwandans in this country have formed a nonprofit organization, The Tutsi Relief Founda- tion Inc., whose main purpose is to aid in any way possible, but with primary emphasis on education and relocation of those who are able to adapt to the changed environment.